2015
DOI: 10.1080/09168451.2015.1025035
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 10 is required for androgen-dependent proliferation of LNCaP prostate cancer cells

Abstract: Androgen receptor (AR) signaling is the master regulator of prostate cell growth. Here, to better understand AR signaling, we searched for AR-interacting proteins by yeast two-hybrid screening and identified protein arginine methyltransferase 10 (PRMT10) as one of the interacting proteins. PRMT10 was highly expressed in reproductive tissues, such as prostate. Immunostaining showed that PRMT10 was expressed in the nucleus of both epithelia and stroma of rat prostate. In human prostate cancer LNCaP cells, PRMT10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The ligand-activated AR binds to the androgen response element within target gene promoters [85] and thus stimulates the transcription of target genes. Coactivators and corepressors are essential for the modulation of AR transactivation [86][87][88][89][90][91]. Exon 1 in the AR gene contains polymorphic CAG and GGN trinucleotide repeats, which affect the transcriptional activity of the AR [92].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The ligand-activated AR binds to the androgen response element within target gene promoters [85] and thus stimulates the transcription of target genes. Coactivators and corepressors are essential for the modulation of AR transactivation [86][87][88][89][90][91]. Exon 1 in the AR gene contains polymorphic CAG and GGN trinucleotide repeats, which affect the transcriptional activity of the AR [92].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Mutating K311 also caused a significant increase in the drug metabolism pathway. Androgen receptor activity has previously been linked to arginine metabolism with AR interacting with protein arginine methyltransferase 10 (PRMT10) (31), similarly PRTM6 was reported to co-activate the AR (32), conversely AR deficiency alters the arginine-vasopressin sexually dimorphic system (33). …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that PRMT2, one of the protein arginine methyltransferase family members, was recruited by and acted as a coactivator of AR in the presence of androgens [ 10 ]. Protein arginine methyltransferase 10 was also down regulated by AR [ 11 ]. Research also showed that PRMT6 could methylate and interact with AR, and that the interaction between them was obviously enhanced when AR was mutant [ 12 ].…”
Section: Introductionmentioning
confidence: 99%